WANPRESTASI (DEFAULT/BREAKING PROMISE) IN SHARIA BUSINESS LAW - dina nurfitri (Jurnal Ilmiah Pesantren, 2022)
Agreements that are binding will result in certain laws that there will be prestasi and wanprestasi, dispute resolution of wanprestasi can be differentiated into two namely litigation and nonlitigation lines. The default settlement of Sharia banking products can be done by process with extension of credit term, reconditioning is by changing the requirements, restructuring by increasing the amount of credit, combination by combining the three and last collateral foreclosures. The basic provisions that can be learned from the Islamic law of wanprestasi is a legal event which is a form of offence if done with an element that is intentional or done because of negligence caused by overmacht (force majeure). The importance of adh-dhaman (guarantees) in the agreement, so that in agreements that have been approved by both parties there is no dispute. All losses either occur before or after the contract is then borne by the risk by the indemnified party. However, in terms of fiqh Islamist does not punish people who accidentally and do not want such negligent deeds, as long as the man has made the maximum to fulfill his achievements, and Islam appreciates the person who gives room in debt payments. In order to know how to respond to wanprestasi in Sharia business law, such as what Islamic law views wanprestasi and what needs to be done by Islamic Financial Institutions (LKS) when there is a wanprestasi, the author conducts a study on this to enrich knowledge related to the resolution of business disputes in sharia economy.